Substitution Biscuits Red Bean Flour (Phaseoulus vulgaris L.) and Moringa Leaf Flour (Moringa oleifera L.) for Hypercholesterolemia Sufferers on Nutrient Contents and Organoleptic Quality - Safitri, Oktavia Indri; Suwita, I Komang; Razak, Maryam (Politeknik Kesehatan Kemenkes Malang, 2024)
Abstract Background: Increased cholesterol contents can cause health problems such as gallstones, hypertension, stroke and heart attack. According to WHO (2019), globally, hypercholesterolemia is the third cause of ischemic heart disease. It is estimated that worldwide, increased cholesterol can cause 2.6 million deaths. In Indonesia, based on Basic Health Research (Riskesdas) data, the prevalence of hypercholesterolemia sufferers aged over 15 years in 2013 was 35.9% and the prevalence decreased in 2018 by 28.8% (Riskesdas, 2018). The management of hypercholesterolemia is through medical nutrition therapy. The development of biscuit processing is based on the snack needs of hypercholesterolemia sufferers. Objective: Analyze the effect of substitution of red bean flour (Phaseoulus vulgaris L.) and moringa leaf flour (Moringa oleifera L.) on nutrient contents and organoleptic quality. Design: This research used a Completely Randomized Design (CRD) research type using 4 treatment levels with 3 repetitions, namely P0 (100:0:0), P1 (60:5:35), P2 (60:10:30), and P3 ( 60:15:25). Results: The best standard treatment P1 (60:5:35) is the best standard treatment with a recommended serving of 60 grams (6 pieces) with an energy content of 235,1 Kcal, 5,6 grams of protein, 3,5 grams of fat, 45,4 grams of carbohydrates, and 1,3 grams of fiber. Conclusions: The substitution of red bean flour biscuits and Moringa leaf flour had a significant effect on water content, ash content, protein content, fat content, carbohydrate content, fiber content, energy content, color, aroma, taste and texture. Keywords: Hypercholesterolemia, Biscuit, Red Bean Flour Biscuits, Moringa Leaf Flour